Peningkatan Prestasi Belajar Tematik melalui Media Powerpoint Siswa Kelas V Semester Genap SDN Jemur - Sudiono; Suratman; Mrih Handayani; Rosidah Aliim Hidayat (Jurnal Ilmiah Profesi Guru (JIPG), 2021)
Based on observations of student activities who passively participate in the learning process and the lack of variety of teachers in using the media affect the low learning achievement. The purpose of this study is to determine the increase in student achievement in thematic learning using powerpoint media. Classroom Action Research (CAR) was carried out in two cycles. Each cycle consists of two lessons. One cycle consists of 4 activities, namely the stages of planning, implementation, observation, and reflection. The subject of the study was class V SDN Jemur with a total of 20 students consisting of 12 male students and 8 female students. Data collection techniques using tests and documentation. The data analysis technique used descriptive analysis. The results of the research on learning achievement in the Post Test Cycle I, the average completeness obtained is 60%, as many as 12 students exceed the KKM. In the second cycle, the average post-test completeness was 90% as many as 18 students exceeded the KKM. It can be proven that there is an increase in the percentage from cycle I and cycle II, which is 30%. In the second cycle the average 90% completeness exceeds the success indicator, which is 75%. Keywords: learning achievement, powerpoint, thematic